Plastic debris collars: An underreported stressor in tropical reef fishes. Issue 2 (April 2018) - Nunes, Joséde Anchieta C.C.; Sampaio, Cláudio L.S.; Barros, Francisco; Leduc, Antoine O.H.C.
Abstract: Plastic debris collar wrappings (PDCW) are involved in the frequent entanglement of several groups of marine animals. In fishes, however aside from 'ghost fishing', PDCW events are rarely documented, and no record of this occurrence exists in tropical reef fishes. Here, we present records for four species afflicted by plastic debris collars. Observations occurred during snorkeling, and included the silver mojarra Eucinostomus argenteus, Atlantic thread herring Ophistonema oglinum, tomtate grunt Haemulon aurolineatum and gray parrotfish Sparisoma axillare . While PDCW may not create an instantaneous source of mortality, our observations suggest that debilitating stress, created by reduced swimming performances, feeding and/or antipredator behavior are likely consequences for afflicted individuals. Given the importance of these performances on survival, reduction in fitness is expected. This note aims to report cases of PDCW and underscore that such interactions between fishes and plastic pollution may be more prevalent than previously expected in coastal reef habitats. Highlights: Plastic debris collar wrappings (PDCW) are involved in the frequent entanglement of several groups of marine animals. We present records for four species afflicted by plastic debris collars. PDCW reduced fish swimming performances, feeding and antipredator behavior. Given the importance of these performances on survival, reduction in fitness is expected.